Defining and Estimating a Trading Area - Huff, David L. (Journal of Marketing, 1964)
What are the conceptual properties of a trading area? What is the definition of the term? What testable propositions are currently available to validate its properties and thus give precision to the definition? This article gives answers to these questions.